2020
DOI: 10.33750/ijhi.v3i3.87
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pandemic on Homebased Tourism: Post Covid-19

Abstract: The present study explores the effect of a pandemic on home-based tourism and tourists' decision to appreciate and patronize local indigenous sites, theater, and other tourism activities. An increase in the global spread of COVID-19 pandemic and incessant rise in deaths especially in renowned destinations, travel restrictions and subsequent closure of international tourist sites; have pulled Nigerian tourists’ motivation away from international destinations. A survey of 250 frequent Nigerian travelers reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…According to WHO (2020) Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (Umukoro et al, 2020;Udok et al, 2020).On the other hand, Hui et al (2020) stated that the disease was first identified in December 2019 in Wuhan, the capital of China's Hubei province, and has since spread globally, resulting in the ongoing 2019-20 coronavirus pandemic (Bassey 2020;Bassey & Eyo 2020).…”
Section: Covid 19mentioning
confidence: 99%
“…According to WHO (2020) Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (Umukoro et al, 2020;Udok et al, 2020).On the other hand, Hui et al (2020) stated that the disease was first identified in December 2019 in Wuhan, the capital of China's Hubei province, and has since spread globally, resulting in the ongoing 2019-20 coronavirus pandemic (Bassey 2020;Bassey & Eyo 2020).…”
Section: Covid 19mentioning
confidence: 99%
“…It is reported that in Nigeria, for instance, millions of people observing COVID-19 lockdown lack food and income their various families need to survive since it is from the income of the daily toils of the larger percentage of the population that they get food, water, healthcare, and other basic needs. Indeed, the disadvantaged and marginalized group's precarious situation cannot be estimated (Umukoro et al, 2020).…”
Section: The Condition Posed By Covid-19 Pandemicmentioning
confidence: 99%
“…During their pastoral vocations, most pastors are not usually provided with housing or other necessities. Many people, however, find themselves in a financial bind when they near or achieve retirement, owing to obstacles that sometimes outnumber those faced by other professionals (Aaron¸2010; Umukoro et al, 2020). Some are struggling to make ends meet due to a lack of home equity and a pension, while others are staying on the job longer out of dread of the unknown.…”
Section: Introductionmentioning
confidence: 99%